A retrospective observational study of vCare: a virtual emergency clinical advisory and transfer service in rural and remote Australia - Kimberley Dean; Cynthia Chang; Erin McKenna; Shannon Nott; Amanda Hunter; Julie A. Tall; Madeline Setterfield; Bridget Addis; Emma Webster (BMC, 2024)
Abstract Background Provision of critical care in rural areas is challenging due to geographic distance, smaller facilities, generalist skill mix and population characteristics. Internationally, the amalgamation telemedicine and retrieval medicine services are developing to overcome these challenges. Virtual emergency clinical advisory and transfer service (vCare) is one of these novel services based in New South Wales, Australia. We aim to describe patient encounters with vCare from call initiation at the referring site to definitive care at the accepting site. Methods This retrospective observational study reviewed all patients using vCare in rural and remote Australia for clinical advice and/or inter-hospital transfer for higher level of care between February and March 2021. Data were extracted from electronic medical records and included remoteness of sites, presenting complaint, triage category, camera use, patient characteristics, transfer information, escalation of therapeutic intervention and outcomes. Data were summarised using cross tabulation. Results 1,678 critical care patients were supported by vCare, with children (12.5%), adults (50.6%) and older people (36.9%) evenly split between sexes. Clinicians mainly referred to vCare for trauma (15.1%), cardiac (16.1%) and gastroenterological (14.8%) presentations. A referral to vCare led to an escalation of invasive intervention, skill, and resources for patient care. vCare cameras were used in 19.8% of cases. Overall, 70.5% (n = 1,139) of patients required transfer. Of those, 95.1% were transferred to major regional hospitals and 11.7% required secondary transfer to higher acuity hospitals. Of high-urgency referrals, 42.6% did not receive high priority transport. Imaging most requested included CT and MRI scans (37.2%). Admissions were for physician (33.1%) and surgical care (23.3%). The survival rate was 98.6%. Conclusion vCare was used by staff in rural and remote facilities to support decision making and care of patients in a critical condition. Issues were identified including low utilisation of equipment, heavy reliance on regional sites and high rates of secondary transfer. However, these models are addressing a key gap in the health workforce and supporting rural and remote communities to receive care.